Utilização da plataforma de prototipação de hardware arduino como apoio à aprendizagem de conceitos do componente curricular de programação do ensino médio - Soares, Renira Carla (2016)
From the compelling need of school to become more attractive to the students, it seeks to stimulate the practices that approach the school contents to the reality, as an alternative to innovate the learning. From the premise that the teaching of algorithm in high school in the traditional way is a hard task in schools, the present work aims to verify the efficiency of the insertion of arduino hardware prototyping platform as Information and Communication Technology to support the process of teaching and learning in the classroom. This work, proposed in the Postgraduate Program in Educational Technologies in Network, in particular in the research line of Development of Educational Technologies in Network, suggests the insertion in traditional methods of teaching of this programmable platform of hardware capable of becoming a support, school help, complementation of class, in order to involve the student, through the exploration of his or her curiosity, associated to the contact and handling of the equipment, in the longing that it substitutes the role of spectator by the leading role in the process of teaching and learning. The educational product described in this work is about five objects of learning constructed from the Arduino hardware, to assist in the comprehension of covered contents in the subject of Programming I in the Technical Computing Course in the campus of IF Farroupilha in Santo Augusto. Each one of the OL (objects of learning) was built to the light of Bloom Taxonomy, which standardizes the language in which the objectives of learning are presented. The other methods used are the ones of qualitative approach and case study. Each object was presented to the students in different pedagogical moments in order to, from each experiment, present one of the contents that introduces the teaching of algorithms. The instruments to conduct the search were based on ethnographic techniques of audio and video recording, besides textual summary, where there was the pedagogical intervention of the researcher, presenting the experiments to the students, which were distributed in pairs or trios. The systemization of data was performed observing the Discursive Textual Analysis, having in mind the need of comprehension of the process. It was possible to realize that the use of experiments in the classroom aroused the interest in the students, in addition to a bigger degree of compromise in the attempt of the students to comply with what was proposed and understand what was happening in each situation problem. The experiments served as a support tool in the learning because the students engaged themselves in the task of discovering in group the correct words to comprehend the meaning of each experiment and systematize it through a textual description and subsequently a pseudocode. It is believed that because of the popularity of Arduino, facility of construction of experiments and because of the fact of being a free technology it is possible to characterize the objects of learning as a viable alternative as a didactic resource to the teaching of algorithms, taking advantage of its potential in public schools, usually lacking in resources.